THE ROLE OF USING INSTAGRAM FOR INCREASING VOCABULARY AND LISTENING SKILL AMONG ESL/EFL LEARNERS (Educator Insights: Journal of Teaching Theory and Practice, 2025)
This study looks at how Instagram can help ESL/EFL students improve their English vocabulary and listening skills. It talks about the platform's multimodal environment, which includes videos, captions, hashtags, and interactive features that give learners real language input in interesting, real-world situations. Research shows that seeing Instagram content like Reels, stories, and educational accounts helps with incidental learning, helps people remember what they've learned, and encourages them to practice their vocabulary and listening skills. The study also stresses the importance of using social media responsibly and encourages students to only interact with content that helps them learn a language. The results show that Instagram is a dynamic, learner-centered platform that works well with formal classroom instruction and encourages informal, self-directed learning.